Interfacility Transfer for VA-ECMO in Beta Blocker and Calcium Channel Blocker Overdoses: A Report of Two Cases - Richard Fisher; Santiago Batista Minaya; Heather Brunette; Joshua Nogar; Payal Sud (Clinical Practice and Cases in Emergency Medicine)
Introduction: Calcium channel blocker (CCB) and beta blocker (BB) overdoses are life-threatening conditions that can lead to vasoplegic and cardiogenic shock. Treatment involves a combination of vasopressors, calcium, glucagon, and/or high-dose insulin euglycemia therapy. The most severe overdoses may require venoarterial extracorporeal membrane oxygenation (VA-ECMO), which often results in interfacility transfers. This report describes two successful VA-ECMO transfers for refractory CCB/BB overdose. Case Reports: Case 1: A 56-year-old male developed severe hypotension after ingesting 40–45 tablets of 10 milligram (mg) amlodipine tablets. After initial treatment approaches were unsuccessful, an early interdisciplinary discussion facilitated timely cannulation at the initial facility and quick transfer for VA-ECMO initiation. The patient was discharged at his neurological baseline after 60 days. Case 2: A 19-year-old female presented to the emergency department after a polypharmacy ingestion including 60 tablets of 20 mg propranolol. An early interdisciplinary discussion between the medical intensive care unit, medical toxicology, and the ECMO team allowed for prompt transfer directly to the receiving hospital catheterization lab for VA-ECMO within three hours of the initial presentation. The patient was discharged to an inpatient psychiatric facility after nine days. Conclusion: Venoarterial extracorporeal membrane oxygenation for refractory shock due to CCB and BB overdoses can be a life-saving intervention. Interfacility transfer of poisoned patients for VA-ECMO is logistically challenging, which can delay the appropriate care for patients with an otherwise morbid prognosis. A streamlined interfacility transfer protocol with multidisciplinary collaboration can help optimize outcomes.